Effects of nursing intervention models on social adaption capability development in preschool children with malignant tumors: a randomized control trial. Issue 6 (1st May 2014) - Yu, Lu; Mo, Lin; Tang, Yan; Huang, Xiaoyan; Tan, Juan
Abstract Objectives The objectives of this study are to compare the effects of two nursing intervention models on the ability of preschool children with malignant tumors to socialize and to determine if these interventions improved their social adaption capability (SAC) and quality of life. Methods Inpatient preschool children with malignant tumors admitted to the hospital between December 2009 and March 2012 were recruited and randomized into either the experimental or control groups. The control group received routine nursing care, and the experimental group received family‐centered nursing care, including physical, psychological, and social interventions. The Infants‐Junior Middle School Student's Social‐Life Abilities Scale was used to evaluate SAC development of participants. Results Participants (n = 240) were recruited and randomized into two groups. After the intervention, the excellent and normal SAC rates were 27.5% and 55% in the experimental group, respectively, compared with 2.5% and 32.5% in the control group (p < 0.001). After the intervention, SAC in experimental group was improved compared with before intervention (54.68 ± 10.85 vs 79.9 ± 22.3, p < 0.001). However, no differences in SAC were observed between baseline and after intervention in the control group (54.70 ± 11.47 vs. 52 ± 15.8, p = 0.38). Conclusion The family‐centered nursing care model that included physical, psychological, and social interventions improved the SAC of children with malignancies compared with children receiving routine nursing care. Establishing a standardized family–school–community–hospital hierarchical multi‐management intervention model for children is important to the efficacy of long‐term interventions and to the improvement of SAC of children with malignancies. Copyright © 2014 John Wiley & Sons, Ltd.